KETERCAPAIAN STANDAR NASIONAL PENDIDIKAN DI SEKOLAH MENENGAH ATAS - Lia Yuliana; Sabar Budi Raharjo (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2019)
This study aims to determine the achievement of National Education Standards (SNP) based on accreditation data and the inhibitors in achieving National Education Standards at the high school level. A quantitative descriptive was used in this research. Data obtained from school principals, school supervisors, and education officers at the secondary education level. Data was obtained from guided discussion gathered with school principals, school supervisors, education officer representatives, and resource persons from academics and practitioners. Respondents were taken based on purposive sampling with the aim at accredited A schools in urban areas. Secondary data obtained from BAN-SM, whereas the primary data obtained from the implementation of eight National Education Standards. School with A grade in accreditation is assumed could provide information on the difficulties and obstacles in the implementation of the National Education Standards. The finding showed that based on 2017 accreditation there were three educational standards with the lowest achievements namely, Educator and Educational Staff Standards (PTK), Facilities and Infrastructure Standards and Graduates Competency Standards. It was also found that there are obstacles in achieving standards at the education unit level. Standards that are difficult to achieve are Educator and Educational Staff Standards, Facilities and Infrastructure Standards, and Financing Standards. Schools accept these standards so that the fulfillment of these standards depends on the quota given by the government.Abstrak Penelitian ini bertujuan untuk mengetahui capaian Standar Nasional Pendidikan berdasarkan data akreditasi dan hambatan dalam pencapaian Standar Nasional Pendidikan jenjang Sekolah Menengah Atas. Penelitian menggunakan metode deskriptif kuantitatif. Data diperoleh dari kepala sekolah, pengawas sekolah, dan cabang dinas pendidikan pada jenjang pendidikan menengah. Data diperoleh dari kegiatan diskusi terpimpin dengan kepala sekolah, pengawas sekolah, perwakilan cabang dinas, dan berdasarkan purposive sampling pada sekolah yang terakreditasi A pada daerah perkotaan. Data sekunder diperoleh dari BAN S/M. Sedangkan data primer diperoleh dari implementasi delapan Standar Nasional Pendidikan. Hasil penelitian menunjukkan bahwa pada jenjang SMA berdasarkan akreditasi 2017 ada tiga standar pendidikan yang capaiannya paling rendah yaitu Standar Pendidik dan Tenaga Kependidikan, Standar Sarana dan Prasarana, dan Standar Kompetensi Lulusan. Hambatan yang ditemui dalam pemenuhan standar pada tingkat satuan pendidikan yaitu terutama pada Standar Pendidik dan Tenaga Kependidikan, Standar Sarana dan Prasarana, dan Standar Pembiayaan. Dengan demikian, belum semua standar pendidikan dapat dipenuhi oleh sekolah tetapi pada sekolah swasta yang mandiri standar pendidikan dapat dicapai dengan baik.